2009
DOI: 10.1161/circulationaha.108.809566
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time 3-Dimensional Echocardiography Provides New Insight Into Mechanisms of Tricuspid Valve Regurgitation in Patients With Hypoplastic Left Heart Syndrome

Abstract: Background-Tricuspid regurgitation in hypoplastic left heart syndrome has an impact on outcome, but its mechanisms remain unclear. Methods and Results-Real-time 3-dimensional echocardiography was performed in 35 patients with hypoplastic left heart syndrome (age, 1 month to 10 years; 10 after first-stage Norwood, 12 after superior cavopulmonary shunt, 13 after Fontan). From the 3-dimensional data set, we marked the annulus in systole and diastole. At mid systole, we marked the location of the papillary muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 29 publications
1
72
1
Order By: Relevance
“…In hypoplastic left heart syndrome, for example, the absence of a developed LV may alter tricuspid valve annular configuration and worsen tricuspid regurgitation, an important risk factor for adverse outcomes in this population. 105 Likewise, a larger interventricular septum may increase the risk for death or transplantation in this population. 106 This may be yet another manifestation of the effects of ventricular-ventricular interactions on RV function.…”
Section: March 4 2014mentioning
confidence: 99%
“…In hypoplastic left heart syndrome, for example, the absence of a developed LV may alter tricuspid valve annular configuration and worsen tricuspid regurgitation, an important risk factor for adverse outcomes in this population. 105 Likewise, a larger interventricular septum may increase the risk for death or transplantation in this population. 106 This may be yet another manifestation of the effects of ventricular-ventricular interactions on RV function.…”
Section: March 4 2014mentioning
confidence: 99%
“…[8][9][10] Quantitative 3DE permits evaluation of the spatial relationships between the TV annulus, leaflets, and the supporting apparatus by measurement of tethering and prolapse volumes, leaflet and annular areas, and PM angles. 4,11 We have reported the use of quantitative 3DE to assess mechanisms of TR and demonstrated that this technique is able to detect areas of TV tethering and prolapse in HLHS. 4 Previous studies have evaluated mechanisms for TR in HLHS at or beyond the time of the second-stage palliation; however, there is a paucity of literature on TV function before Background-Our purpose was to test the following hypotheses: (1) patients with hypoplastic left heart syndrome who develop significant tricuspid regurgitation (TR) or require tricuspid valve (TV) surgery in the medium term have detectable TV abnormalities by 3-dimensional echocardiography (3DE) prestage 1 palliation and (2) TR is associated with reduced survival and increased TV intervention.…”
Section: Clinical Perspective On P 772mentioning
confidence: 99%
“…This proprietary software was used to develop 3D models of the TV and its apparatus for analysis as described previously. 4,11 Briefly, by using the extracted x, y, and z spatial coordinates, the software defined 2 separate surfaces, one surface that is fit to the TV leaflets and one that is fit to the annulus. The coordinate system was rotated and translated so that the origin (0, 0, 0) is at the center of the annulus and the z axis is perpendicular to the best-fit plane to the annulus, as shown in Figure 1A and 1C, for 2 representative subjects.…”
Section: Three-dimensional Echocardiography Quantificationmentioning
confidence: 99%
See 2 more Smart Citations